Takhrij and Syarah Hadith of Agrotechnology: Study of the Benefits of al-Kam'ah - Mohammad Zinedine Maulidan Rustian; Wahyudin Darmalaksana; Jajang Supritana (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about al-Kam'ah plants. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The result and discussion of this research is that the al-Kam'ah plant was popular at the time of the Prophet. as a plant that can cure various diseases and has properties for the body. The conclusion of this research is takhrij and syarah hadith of the Prophet about al-Kam'ah plants with agrotechnological analysis confirms that al-Kam'ah plants are beneficial for human health.